Acquired bilateral telangiectasia macularis eruptiva perstans: A unique clinical feature of photodamaging rather than a subtype of cutaneous mastocytosis. Issue 11 (23rd June 2017) - Moon, Hye‐Rim; Kim, Young Jae; Jung, Joon Min; Won, Chong Hyun; Lee, Mi Woo; Choi, Jee Ho; Chang, Sung Eun
Abstract: Telangiectasia macularis eruptiva perstans (TMEP) is a rare subtype of cutaneous mastocytosis, characterized by telangiectatic tan to brown macules on the trunk and extremities. Although TMEP has been descried as an uncommon disease in the literature, we often encounter patients with TMEP lesions in the outpatient clinic. We aimed to assess the clinical and histopathological characteristics of acquired bilateral TMEP, and the pathophysiological mechanism of acquired bilateral TMEP among these patients. We retrospectively reviewed 30 patients (28 men and 2 women) with acquired bilateral TMEP; multiple telangiectatic dark red to brown macules that were symmetrically distributed. The clinical characteristics and general histopathological findings of lesional skin were investigated. The number of mast cells was evaluated using immunohistochemical analysis with an antibody directed against c‐kit (CD117). Acquired bilateral TMEP was predominantly localized on the sun‐exposed area: the upper arm in 30 patients (100%), forearm in 19 patients (63.3%) and anterior chest in 15 patients (50%). A total of 16 patients (53.3%) showed at least one aggravating factor, including UV irradiation, alcohol use and heat exposure. Compared with the mast cell numbers in 19 age‐ and biopsy site‐matched healthy controls (91 ± 29.0/mm 2 ), the number of mast cells in the papillary dermal skin of acquired bilateral TMEP patients was significantly increased (159 ± 37.2/mm 2, P < 0.01). In addition, a significant difference in vessel numbers in the papillary dermis was observed between acquired bilateral TMEP patients and healthy controls (10.5 ± 1.9 vs 5.4 ± 1.0/mm 2, P < 0.01). Acquired bilateral TMEP is a relatively common disorder in middle‐aged Asian men. An increased number of mast cells and dilated vessels might be a photoaging‐related reactive process of chronic sun‐exposure, which consequently leads to the formation of characteristic telangiectatic hyperpigmentary macules through certain melanogenic mediators.